Influence of coulomb effects on electron dynamics in orthogonally polarized two-color laser fields - Hristina S. Delibašić-Marković; Violeta M. Petrović; Ivan D. Petrović (Results in Physics)
This study examines the ionization dynamics of argon atoms under orthogonally polarized two-color laser fields, highlighting the impact of field strength ratio on ionization rates and electron momentum. Utilizing a theoretical framework, we compare our results with various models to delineate the effects of Coulomb potential across different field strength ratios. The investigation reveals that the distribution of electric field strength over orthogonal components influences the ionization efficiency, with variations in ionization rates and momentum distributions across a range of intensities. Our findings contribute to a deeper understanding of strong-field ionization processes, providing insights into the interplay between field geometry and electron dynamics.